Binary dance rhythm or Quaternary dance rhythm which has the greatest effect on non-motor symptoms of individuals with Parkinson's disease?. (May 2021) - Moratelli, Jéssica; Alexandre, Kettlyn Hames; Boing, Leonessa; Swarowsky, Alessandra; Corrêa, Clynton Lourenço; Guimarães, Adriana Coutinho de Azevedo
Abstract: This study aimed to compare the effect of a binary and quaternary rhythm protocol on cognition, mental activity, daily life, and quality of life among individuals with Parkinson's Disease. A two-arm randomized clinical trial with 31 individuals diagnosed with Parkinson's disease, who were allocated to the binary group or quaternary group. Both groups underwent a 12-week intervention. The following variables were analyzed: personal and clinical information; MoCA; UPDRSI and II; PDQ-39. Both intervention groups improved cognition, mental activity, activities of daily living, and quality of life. In addition, there were intergroup differences in total UPDRSII, writing, and hygiene where the quaternary group was superior to the binary group. It concludes that the binary and quaternary rhythm positively influenced and presented similar effects on the complementary treatment of individuals with Parkinson's disease on the studied variables. Thus, it is believed that both interventions are possible and feasible for the health professionals involved in the area. Highlights: Dance is important in the adjuvant treatment of Parkinson's disease. The cognition and mental activity of people with Parkinson's disease can be improved after dance classes. Different dance rhythms show positive results in ADLs and QoL in people who suffer from the disease.